eCM 2021
DOI: 10.22203/ecm.v042a10
|View full text |Cite
|
Sign up to set email alerts
|

Application of a BMP2-binding heparan sulphate to promote periodontal regeneration

Abstract: Periodontitis is the most common inflammatory disease that leads to periodontal defects and tooth loss. Regeneration of alveolar bone and soft tissue in periodontal defects is highly desirable but remains challenging. A heparan sulphate variant (HS3) with enhanced affinity for bone morphogenetic protein-2 (BMP2) that, when combined with collagen or ceramic biomaterials, enhances bone tissue regeneration in the axial and cranial skeleton in several animal models was reported previously. In the current study, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…[41][42][43] Their critical role in transforming growth factorβ and bone morphogenetic protein signaling has not been as widely explored in periodontal ligament homeostasis as in bone. [44][45][46] Particularly for heparan sulfate, it has been demonstrated that the degree of sulfation of heparan sulfate can impact the strength of the electrostatic interactions between heparan sulfate proteoglycans and bone morphogenetic proteins. 47 However, the binding of bone morphogenetic proteins to heparan sulfate proteoglycans does not entirely depend on sulfated glycosaminoglycans.…”
Section: Proteoglycans and Glycosaminoglycans In Periodontal Ligamentmentioning
confidence: 99%
See 3 more Smart Citations
“…[41][42][43] Their critical role in transforming growth factorβ and bone morphogenetic protein signaling has not been as widely explored in periodontal ligament homeostasis as in bone. [44][45][46] Particularly for heparan sulfate, it has been demonstrated that the degree of sulfation of heparan sulfate can impact the strength of the electrostatic interactions between heparan sulfate proteoglycans and bone morphogenetic proteins. 47 However, the binding of bone morphogenetic proteins to heparan sulfate proteoglycans does not entirely depend on sulfated glycosaminoglycans.…”
Section: Proteoglycans and Glycosaminoglycans In Periodontal Ligamentmentioning
confidence: 99%
“…Given the new tools available to generate such therapeutics, a clear safety profile and the ability to manufacture it at low cost, human translational studies should soon be underway. 45…”
Section: Tissue Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…Recombinant human BMP-2 (rhBMP-2) was approved for use for accelerating bone fusion in slow-healing fractures [ 394 ]. In addition, rhBMP-2 was used to treat periodontal wound healing and new bone formation in the maxilla and mandibles of animals and humans [ 395 , 396 , 397 , 398 , 399 , 400 , 401 , 402 , 403 ].…”
Section: Therapeutic Implications Of Bmps For Endodontic Regenerationmentioning
confidence: 99%